Analisis Implementasi Kepemimpinan Instruksional Kepala Sekolah Terhadap Kinerja Mengajar Guru di SD Islam Nurul Huda Kabupaten Bekasi - Hoerudin, Ahmad; Kurniady, Dedy Achmad; Sudarsyah, Asep (Jurnal Tata Kelola Pendidikan, 2024)
Instructional leadership is a leadership model oriented towards the process and outcomes of student learning through empowering teachers professionally. This research aims to describe the role of instructional leadership played by the school principal and the teaching performance of teachers at Nurul Huda Elementary School, Setu District, Bekasi Regency. Through a qualitative approach involving 4 respondents, this study focuses on analyzing the implementation of instructional leadership by the school principal towards the teaching performance of teachers in the school. The results of this research describe the positive school climate and enforcement of rules also as a focus of the school principal's instructional leadership. However, challenges arise in the form of limited learning time allocation, which restricts teachers' ability to plan learning deeply. In this context, strong instructional leadership can be a crucial factor in improving teaching performance and learning quality. Therefore, school principals can take guidance from instructional leadership models emphasizing academic activities and student learning outcomes through optimal teacher empowerment